Burden of Risk Factors for Cervical Cancer Among Women Living in East Africa: An Analysis of the Latest Demographic Health Surveys Conducted Between 2014 and 2017 - Abila, Derrick Bary; Wasukira, Sulaiman Bugosera; Ainembabazi, Provia; Wabinga, Henry (JCO Global Oncology, 2021)
In East Africa, cervical cancer is a leading cause of morbidity and mortality among women diagnosed with cancer. In this study, we describe the burden of risk factors for cervical cancer among women of reproductive age in five East African countries. For each country, using STATA13 software and sampling weights, we analyzed the latest Demographic and Health Survey data sets conducted between 2014 and 2017 in Burundi, Kenya, Rwanda, Tanzania, and Uganda. We included women age 15-49 years and considered six risk factors (tobacco use, body mass index, age at first sexual intercourse, age at first birth, number of children, and hormonal contraceptive use). Of the 93,616 women from the five countries, each country had more than half of the women younger than 30 years and lived in rural areas. Pooled proportion of women with at least one risk factor was 89% (95% CI, 87 to 91). Living in a rural area in Burundi (adjusted incidence rate ration 0.94; 95% CI, 0.9 to 0.99; P = .019) and Rwanda (adjusted incidence rate Ration 0.92; 95% CI, 0.88 to 0.96; P < .001) was associated with a lower number of risk factors compared with living in an urban area. In all the countries, women with complete secondary education were associated with a lower number of risk factors compared with those with no education. This study reveals a high burden of risk factors for cervical cancer in East Africa, with a high proportion of women exposed to at least one risk factor. There is a need for interventions to reduce the exposure of women to these risk factors.